Jackstone: A Calculus “Toy” in the Bladder. A Case Report of Rare Entity and Comprehensive Review of the Literature - Symeonidis, Evangelos N.; Memmos, Dimitrios; Anastasiadis, Anastasios; Mykoniatis, Ioannis; Savvides, Eliophotos; Langas, Georgios; Baniotis, Panagiotis; Bouchalakis, Athanasios; Tsiakaras, Stavros; Stefanidis, Panagiotis; Stratis, Michail; Mutomba, Wilbert F.; et al. (Acta medica Lituanica, 2022)
Background: An uncommon type of urinary calculus, Jackstone was named after its distinct resemblance to the children’s game “Jacks.” It typically involves the bladder and, to a lesser extent, the upper urinary tract.Case Presentation: Herein, we report a case of Jackstone vesical calculus in a 75-year-old male undergoing elective open prostate surgery for benign prostate hyperplasia refractory to medical treatment. Preoperative clinical examination revealed intermittent gross hematuria and symptoms suggestive of bladder outlet obstruction, while radiological investigation confirmed the presence of a solitary star-shaped spike-like bladder stone along with an overly enlarged prostate. Following open simple prostatectomy and concomitant intact stone removal, our patient made an uneventful postoperative recovery.Conclusion: This case highlights an infrequent subtype of bladder lithiasis and further expands upon the importance of promptly treating the underlying cause once this rare entity is detected. A comprehensive review of the literature on Jackstone calculi is further presented.